Study of alternative lubricants for cold extrusion process of A1100 pure aluminum - Mohd. Ahyan, Nurul Aini (Penerbit UTM Press, 2014)
Lubrication in metal forming process is very important to control wear and friction at the interface between interacting surfaces. Non-renewable resources, such as mineral oil are widely used since a beginning due to its ability to act as a supplier to the wearing contact which functions as a film material or sustains chemical transformation to become a film material. Since it is will not last for a few more decades, renewable resources had been studied in order to find an alternative lubricant with presents similar results in terms of extrusion load and product quality. Two renewable lubricants were analyzed (Palm Kernel and Palm Stearin) together with additive free paraffinic mineral oil VG460 will act as a comparison lubricant. The experiment used a cold work plane strain extrusion apparatus consisting of a pair of taper die and a symmetrical work piece (billet). The billet material was annealed pure aluminum A1100 with radius of 5mm at the deformation area. It was found that palm Palm Kernel and Palm Stearin performed slightly high extrusion load, however they show no severe wear on product surface. Based on the results, it is proven that renewable based lubricants can be considered as a substitute to common mineral based lubricants used in the industry.